(untitled) (Fiep Bulletin - online, 2015)
Coronary artery disease is a pathology that causes abnormalities of the coronary arteries, which causes more prevalent is the atherosclerotic process. The formation of atherosclerosis changes the compliance of coronary vessels and their hemodynamics in which culminates with the disorder in coronary flow control. Myocardial ischemia raises limitations to patients and decreased myocardial perfusion, in a manner that promotes the reduction of daily activities. The objective of this study was to identify the main effects of aerobic exercise on Biomolecular and funcional parameters change of patients with coronary artery disease. Were made to the database queries of Pub Med, Scielo and periodicals in the area of Cardiology (AHA and SBC) using the keywords atherosclerosis, aerobic exercise, coronary artery disease and their translations into English, the past 15 years (1997-2012). One of the main functional adaptations include the increase in peak VO2, increased ventilatory threshold anaerobic, maximum heart rate and resting heart rate; Biomolecular adaptations are bound to lipid profile and bioavailability nitric oxide. The aerobic exercise is a therapeutic intervention and pharmacological not that contributes to improving the health status of patients with Coronary artery disease through adjustments in biomolecular and functional levels.